Optimization of the Production Pressure for Hydrate Dissociation by Depressurization - Li, Xiao-Yan; Li, Xiao-Sen; Wang, Yi; Zhang, Yu (Energy & Fuels, 2020)
Natural gas hydrate is considered as a promising energy resource in the future. How to choose a suitable production pressure is a key issue when depressurization is taken as the production way of gas hydrate. In this study, we conducted the experiments of methane hydrate dissociation under different production pressures. The influences of production pressure on the hydrate dissociation rate and the method to optimize the production pressure were studied. The experimental results illustrated that two stages were contained in the hydrate dissociation by depressurization: the depressurization stage (DS) and the constant pressure stage (CPS). In the DS, the sensible heat of the sediments was used for hydrate dissociation, and the hydrate dissociation amount increased with the decrease of the production pressure. In the CPS, the required heat for hydrate dissociation was transferred from the surroundings. As the production pressure decreased, the hydrate dissociation rate increased. Although the lower production pressure can improve the hydrate dissociation rate, the energy input of hydrate production in field for depressurization with the lower production pressure could be larger than that with the higher production pressure. In order to improve the production efficiency, an optimizing method of production pressure was first proposed. Based on the experimental data, the optimum production pressure was calculated with this method. The calculation result indicates that the production pressure should be as close to the pressure of hydrate quadruple point (2.56 MPa) as possible. Moreover, it is worth noting that the optimum production pressure in field production could be different from that obtained by experiments because the optimum production pressure is determined by the actual function of the energy input in field. However, the evaluation method is universal.